Vicariant speciation due to 1.55 Ma isolation of the Ryukyu islands, Japan, based on geological and GenBank data. Issue 3 (27th May 2013) - Osozawa, Soichi; Su, Zhi‐Hui; Oba, Yuichi; Yagi, Takashi; Watanabe, Yasushi; Wakabayashi, John
Abstract The Ryukyu island arc, originally a continental margin arc, separated from the Chinese continent by the rifting of the Okinawa trough, a process which began at 1.55 million years ago (Ma) and continues to the present. In addition, the Ryukyu arc was simultaneously divided into the northern Amami–Okinawa and southern Yaeyama islands by the Kerama rift valley, and consequently formed two isolated island units. The Kuroshio warm current began to flow into the Okinawa trough from the Yonaguni Strait, and flow out through the Tsushima and Tokara straits also at 1.55 Ma, and these seaways effectively acted as barriers between the Ryukyu islands and Taiwan, China and Japan. Through this geological process, vicariant speciation generated Ryukyu endemic animal species. We support this hypothesis by drawing linearized maximum likelihood (ML) phylogenetic trees of the species in four endemic insect groups (peacock butterfly, Chinese windmill butterfly, golden‐ringed dragonfly, window firefly) using GenBank sequence data. We determined the precise branching ages for these phylogenetic trees, and show simultaneous speciation at 1.55 Ma for Amami–Okinawa and Yaeyama units. The Taiwan and Tsushima straits, barriers between Taiwan and China, and Japan and Korea, respectively, did not form sufficient barriers to migration during glacial low stands, and species were intermingled. A marine embayment may have posed as a migration barrier between northern and southern China in the Quaternary or a little earlier. From our study we also estimate the precise molecular evolution rate and justify the molecular clock.